Investigating successful kickout performance in senior inter-county Ladies Gaelic Football - McColgan, A.; Bradley, J.; McKenna, O.; Byrne, A.; Twomey, L.; Gaul, D.; Martin, D. (International Journal of Performance Analysis in Sport, 2025)
Despite an increase in participation in female sports there remains a gender data gap in sport science research. Ladies Gaelic Football (LGF) is a case in point with just one paper investigating successful match play performance. This study investigates successful kickout (KO) performance in senior inter-county LGF. Eighty-three games (3081 kickouts) were analysed from the 2019-2023 TG4 All-Ireland Senior LGF Championship using NacSport Scout. Statistical differences between winning and losing performances were identified using paired sample t-tests (p < 0.05) and Wilcoxon signed ranked tests (p < 0.05). KOs were shown influence match outcome with winning teams performing significantly better on their own and opposition KOs. A KO "drop zone" between the 21 and 65 m lines was identified with winning teams performing significantly better at retaining and scoring from their own an opposition KOs. Distribution time emerged as a critical factor, with faster KOs linked to increased retention and shot/score creation. Analysis strongly suggests that LGF teams use strategies and structures to optimise retention of their own and opposition KOs.The current study is the first to provide an in-depth insight into successful KO performance in LGF and will be of considerable interest to coaches, performance analysts, and LGF administrators.